Crisis communication in digital contexts: a systematic review of scholarly research and emerging trends - Ana Matias; Ezel Türk; Ana Lopes (Corporate Communications: An International Journal, 2026)
Purpose In the digital era, effective crisis communication has become a cornerstone of organizational resilience, as social media and other digital platforms increasingly shape public perception during crises. This study provides an integrative literature review of academic research on crisis communication in digital environments from 2015 to 2025. Design/methodology/approach The study examines 78 articles from five journals in the Scopus database with the highest CiteScores in the fields of media studies, communication and public relations. This review employs a qualitative content analysis using MAXQDA 24 to code theoretical frameworks, methodological approaches, crisis contexts, platform affordances, crisis actors and public response strategies across communication journals. To provide a systematic overview of patterns in the literature, the coded data were subsequently quantified using frequency and percentage analyses, combining qualitative coding with quantitative reporting. Findings This systematic review demonstrates that research on crisis communication in digital contexts remains predominantly grounded in Situational Crisis Communication Theory, while an emerging trend toward innovative, platform-sensitive models is evident, particularly within journals devoted to new media, reflecting the adaptation of classical frameworks to complex digital environments. From a methodological perspective, quantitative approaches predominate, yet qualitative and mixed-method designs provide critical insights into platform affordances and public response dynamics. Within the contextual domain, corporate and reputational crises occupy central focus, with information vetting and transparency crucial under high uncertainty, whereas misinformation is most salient in political crises. Regarding platform-specific dynamics, social media – and notably Twitter/X – mediates engagement, sentiment and collective coping, while information provision consistently constitutes the dominant strategy across actors. Collectively, these findings underscore the interdependent role of theoretical frameworks, crisis contexts and platform affordances in shaping digital crisis communication. Originality/value Overall, the study moves beyond descriptive mapping by framing crisis communication as a socio-technical system in which theories, crisis contexts and platform affordances are mutually constitutive, shaping both communication effectiveness and perceived legitimacy in digital environments.